Competitiveness of Caribbean financial services and WTO-related negotiating strategies - Bourne, Compton...[et al] (CCS/Regional Negotiating Machinery GeorgetownGY, 1998)
Deals with the general context of negotiations and the evolving WTO Financial Services Regime. Provides important statistical analysis on the evolution, structure and performance of the Caribbean financial services industry. Examines the incidence of entry of new regional and extra-regional firms and the issue of competitiveness within the Caribbean financial services sector. Describes in inventory form the existing legal and regulatory regimes in CARICOM. Deals with possible strategies with respect to Caribbean financial services offers at the WTO. Proffers a model schedule of financial services commitments for Caribbean countries.